Synthesis of 3′‐Fluoro‐tRNA Analogues for Exploring Non‐ribosomal Peptide Synthesis in Bacteria. Issue 3 (13th January 2015) - Iannazzo, Laura; Laisné, Guillaume; Fonvielle, Matthieu; Braud, Emmanuelle; Herbeuval, Jean‐Philippe; Arthur, Michel; Etheve‐Quelquejeu, Mélanie
Abstract Aminoacyl‐tRNAs (aa‐tRNAs) participate in a vast repertoire of metabolic pathways, including the synthesis of the peptidoglycan network in the cell walls of bacterial pathogens. Synthesis of aminoacyl‐tRNA analogues is critical for further understanding the mechanisms of these reactions. Here we report the semi‐synthesis of 3′‐fluoro analogues of Ala‐tRNAAla. The presence of fluorine in the 3′‐position blocks Ala at the 2′‐position by preventing spontaneous migration of the residue between positions 2′ and 3′. NMR analyses showed that substitution of the 3′‐hydroxy group by fluorine in the ribo configuration favours the S‐type conformation of the furanose ring of terminal adenosine A76. In contrast, the N‐type conformation is favoured by the presence of fluorine in the xylo configuration. Thus, introduction of fluorine in the ribo and xylo configurations affects the conformation of the furanose ring in reciprocal ways. These compounds should provide insight into substrate recognition by Fem transferases and the Ala‐tRNA synthetases.